Is there a need for a new governance model for regionalised Fisheries Management? Implications for science and advice. (October 2017) - van Hoof, Luc; Kraus, Gerd
Abstract: Over the years, the breadth and depth of EU marine policy has increased with revisions of the Common Fisheries Policy (CFP) and new legislation like the Marine Strategy Framework Directive (MSFD), Integrated Maritime Policy (IMP) and the Framework for Marine Spatial Planning Directive in Europe (FMSP). Not only do these different policies have different remits and hence scope, they also present a multitude of modes of implementation. Although the CFP and MSFD have many common goals when it comes to conservation and sustainable use of living marine resources, they differ substantially in governance set up and implementation modalities, including the underlying scientific advisory processes and structures. Regional cooperation and coordination is foreseen, but there is no governance model in place to coordinate requests for scientific advice, nor institutions coordinating the activities of advice providers, either across policies or across regions. This results in an increase in uncoordinated requests for scientific advice yet the pool of experts fuelling the advisory system is limited. As a result the European marine scientific advisory system is increasingly under pressure. In this paper the consequences of this problem are analysed and a redesign of the institutional governance setting to accommodate these challenges and make the science and advice system ready for the future is explored.